The acute: chronic workload ratio and injury risk in semiprofessional football players - Seco-Serna, R.; Lago-Fuentes, C.; Barcala-Furelos, M. (International Journal of Sports Medicine, 2024)
The purpose of this study was to analyze the association and predictive capacity between the acute:chronic workload ratio (ACWR) and non-contact injuries in a semiprofessional football team. Seventeen football or soccer players from a Spanish Third Division football team participated voluntarily in this study. A prospective longitudinal study was developed during the 2020/2021 season. Twenty-four weeks were analyzed from October to March, including a regenerative microcycle due to the absence of competition during Christmas. Rate of perceived exertion (RPE) and session-rate of perceived exertion (sRPE) were registered for every training and game session. Afterward, acute and chronic workloads were calculated, and ACWR was subsequently derived from them. Furthermore, non-contact injuries were registered during the period mentioned. The main findings were that there is a poor correlation between the ACWR and non-contact injuries (r=0.069 (p<0.05)), and the use of the ACWR by itself is insufficient to predict the occurrence of non-contact injuries in a semiprofessional football team. Consequently, the ACWR is not an useful predictive tool for injuries in semiprofessional football teams.